Principals as Instructional Leaders: A Study of Classroom Practices in Elementary Schools - Purwa Widiyan, Agung; Herawati, Endang Sri Budi; Sari, Maya Novita; Astuti, Yuni (IJCAR: Indonesian Journal of Classroom Action Research, 2024)
The purpose of this qualitative research was to examine the dimensions of instructional leadership of elementary school principals. Drawing upon semi-structured interviews with three teachers and five school principals from Yogyakarta city, this research analyzed significant statements and created codes to illuminate the dimensions that facilitate learning. Five the analysis of the combined data sources, five overarching dimensions emerged for school principals to effectively run school programs. These prioritized dimensions are: (a) Articulating the school’s vision, (b) Designing a comprehensive curriculum, (c) Modifying professional development, (d) Fostering a positive learning climate, and (e) Implementing diverse supervision approaches. The findings underscore the necessity for the development of school principals' supervision skills due to the multifaceted impact of instructional leadership roles, which are interconnected and collectively influence each dimension.